2020
DOI: 10.1183/23120541.00278-2019
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width: a new tool for the severity prediction of sleep apnoea syndrome in children

Abstract: IntroductionRed cell distribution width (RDW) is a parameter included in the complete blood count which informs about the size of the circulating red blood cell population and its distribution. In adults, an increase in RDW was shown to be associated both with obstructive sleep apnoea (OSA) and with an increase in cardiovascular mortality. The aim of this study was to determine whether RDW is a potential biomarker for screening children with moderate–severe OSA.MethodsAn observational study in snoring patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…There are only a few data sources which describe the dependence between OSA severity and such parameters as MCV, MCH, or MCHC. There is also a possible influence of other medical conditions which have an impact on red blood cell parameters, such as alcohol intake, and vitamin deficiency [22]. Morell-Garcia et al reported that parameters such as MCHC significantly differed between moderate and severe OSA groups; thus, this parameter could be used as a marker of severe OSA [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few data sources which describe the dependence between OSA severity and such parameters as MCV, MCH, or MCHC. There is also a possible influence of other medical conditions which have an impact on red blood cell parameters, such as alcohol intake, and vitamin deficiency [22]. Morell-Garcia et al reported that parameters such as MCHC significantly differed between moderate and severe OSA groups; thus, this parameter could be used as a marker of severe OSA [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high-throughput methods, such as flow cytometry, which have the required quantitative power, lack morphological information [13,16]. It seems evident that multidimensional quantifications of cellular morphology bear a great potential for precision diagnostics [12,15,17,[50][51][52][53][54][55][56]. Up to now, quantitative morphological assessments of leukocytes have mainly focused on neutrophils and lymphocytes, the more abundant immune cell types [15,16,19,20,[57][58][59][60][61][62], while less common cells, like eosinophils, are hardly analyzed in these correlative analyses.…”
Section: Introductionmentioning
confidence: 99%